#### Answer

$53i$

#### Work Step by Step

$i(2 + 7i)(2 - 7i) = i(4 +14i - 14i - 49i^2) = i(4 -49 (-1)) = 53i$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$53i$

$i(2 + 7i)(2 - 7i) = i(4 +14i - 14i - 49i^2) = i(4 -49 (-1)) = 53i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.